The effectiveness of using the Orielly strategy in mathematics achievement among sixth grade students (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the effectiveness of using the Orielly strategy in mathematics achievement for sixth grade students, and to verify the goal of the research, the null hypothesis was developed that there is no statistically significant difference at a level of significance (0.05) between the average scores of the experimental group students who are Teaching them according to the Orielly strategy and the average scores of the pupils of the control group taught according to the usual method of the Post-Achievement Test. The current research was limited to the third, fourth and fifth chapters of the mathematics textbook. The number of the research sample reached (60) students, (30) students for the experimental group and (30) students for the control group, and (131) behavioral goals were formulated for the three levels of Bloom's cognitive levels ( Knowing, understanding, applying) and preparing (42) study plans An achievement test consisting of (30) items of the multiple choice type with four alternatives, verifying its validity and stability, calculating the difficulty factor, discriminatory power, and the effectiveness of the wrong alternatives. To calculate the test stability factor, the test was applied using the (Koder - Richardston K-R20) equation. To process the data, a t-test was used for two independent samples, and the results indicated that there was a statistically significant difference at a level of significance (0.05) in favor of the experimental group in the achievement test, which indicates the effectiveness of O'Reilly’s strategy in raising the level of students ’achievement. Several recommendations and proposals have been developed for future use.